Statement by the Managing Director on the Independent Evaluation Office Report on the IMF and Fragile States. (Policy Papers; Policy Paper ;, 2018)
I welcome the report of the Independent Evaluation Office (IEO) on the IMF and Fragile States. The report recognizes that the Fund has made important contributions in restoring macroeconomic stability, building core institutions, and catalyzing donor support across a diverse range of countries in fragile and conflict situations. The IEO's analysis and findings provide a thorough stock-taking and resonate with staff. Accordingly, I broadly support the IEO's recommendations to make the Fund's engagement with countries in fragile and conflict situations more impactful.